Pengaruh Penambahan Nanokolagen Kulit Ikan Tuna Sirip Kuning (Thunnus albacares) Terhadap Tingkat Penerimaan Panelis pada Formula Bodyscrub - Fadlullah Wahid Harun; Nikmawatisusanti Yusuf; Fernandy M. Djailani (Jambura Fish Processing Journal, 2026)
This study aimed to formulate and characterize a body scrub containing nanocollagen derived from yellowfin tuna skin (Thunnus albacares) as an active ingredient to improve cosmetic product quality. The research was conducted using an experimental method with a Completely Randomized Design (CRD) consisting of three nanocollagen concentrations, namely 1 g (D2), 2 g (D3), and 3 g (D4), each with two replications. The observed parameters included organoleptic properties (appearance, texture, aroma, sensation during and after application). Organoleptic data were analyzed using the Kruskal–Wallis test followed by Duncan’s test, while physicochemical data were analyzed using ANOVA. The results showed that the addition of nanocollagen significantly affected (p0.05) organoleptic characteristics, spreadability, and pH of the body scrub. The best formulation was obtained in treatment D3, which exhibited the highest panelist preference with smooth texture, neutral aroma, and good comfort during use.